(untitled) (Statistics, Optimization & Information Computing, 2024)
This paper is concerned with some recurrence relations for single and product moments of doubly truncated power linear hazard rate distribution via generalized order statistics. Some deductions and related results are also considered. The characterization result is provided at the end.